Peran Polri Dalam Menanggulangi Tindak Pidana Penghinaan Dan/Atau Pencemaran Nama Baik Melalui Media Elektronik (Studi di Polda Sumatera Utara) - Raja Lubis, Mhd; Eddy, Triono; Sahari, Alpi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The role of the National Police in tackling criminal acts of humiliation and/or defamation through electronic media is in accordance with the normative role that is in accordance with Police Law Number 2 of 2002. Technological advances show a correlation of increasing crime rates, especially in the field of cyber crime.    The    data    collection    techniques    used    are    interviews    and    literature    study,    the    type    of    data    used    in    this    study    is    primary    data    consisting    of    laws    and    secondary    data    consisting    of    various    kinds    of    reading    materials    related    to    research    titles    such    as    books    on    cyber    crimes.    crime,    articles,    journals    and    literature.  Based on legal research, it can be concluded as follows:  Criminal policies in cyber crimes according to the context of Indonesian criminal law have been regulated in Article 27 Paragraph (3) Junto Article 45 Paragraph (3) Law no. 8 of 2011 as amended by law no. 19 of 2016 concerning Information and Electronic Transactions specifically for perpetrators of criminal acts of humiliation and or defamation through social media. The role of the National Police in tackling criminal acts of humiliation and/or defamation through electronic media, especially in the North Sumatra Regional Police, has been in accordance with its normative role, namely in accordance with Police Law Number 2 of 2002.